The Determinants of Dividend Policy in the US, in a Partial Adjustment Framework - Devereux, Lewis (2018)
The purpose of this dissertation is to analyse and compare two different methods used to forecast the dividends paid by companies. The partial adjustment model has been used within the academic literature for this purpose for over 60 years. Thus, this research aims to test its viability in a modern environment. Rather than sampling from multiple countries, data is obtained from just the US. This avoids the complications associated with different tax regimes in different countries. The US is chosen because it has a large sample size and represents a significant proportion of the global stock market. This analysis adds to the literature concerning millions of investors across the world. The literature review analyses the empirical research regarding dividend payments and develops relationships between the findings and the existing theory. Furthermore, the models used in the literature are examined and adapted for use in this research. Initial predictions are made concerning the coefficients expected from the regressors. The summary statistics following this strengthen some predictions but weaken others. Finally, the simple regression model and the partial adjustment model are run. The findings for the simple regression model are mixed- some are consistent with the theory, but some are not. Size, liquidity, and leverage are statistically significant estimators, with the latter two having the expected sign. Retained earnings, risk, and profitability show to be insignificant variables. This result brings into question the use of the proxies representing firm characteristics. The partial adjustment model shows statistical significance in each variable, with the expected signs. The coefficients are feasible but differ slightly from those found in the literature. The results provide evidence for theories regarding dividend policy, including the aversion to reduce dividends. Further research may analyse the values for the target payout ratio and speed of adjustment, to determine whether they change over time, or with the macroeconomic climate.